Determinant Factors of Taking Anti-Filarial Medication Behavior in the First Round of the Mass Drug Administration Program with Ivermectin, Diethylcarbamazine Citrate, Albendazole: A Cross Sectional Study - Ikrimah Nafilata; Tri Yunis Miko Wahyono; Taniawati Supali (Future Science, 2023)
Filariasis is still endemic in Indonesia with the criteria for a microfilaria rate of >1%, therefore WHO extended the Mass Drug Administration (MDA) program with Ivermectin, Diethylcarbamazine Citrate, Albendazole (IDA). Pekalongan City is one of the filariasis endemic areas in Central Java, Indonesia, which will receive an extension of the MDA program in 2021 and 2022, with a survey coverage of <65% of the population. The study aimed to prove the determinant factors associated with IDA drug-taking behavior to increase treatment coverage. Community-Based Survey conducted in 10 villages in 3 sub-districts in Pekalongan City with a Cross Sectional design using a structured questionnaire interview method, and a sample size of 546 respondents using Probability Proportional to Size and was taken by simple random sampling. Data analysis used the Chi Square statistical test and Logistic Regression. The age distribution of respondents > 42 years dominated by 54,0%, Female Gender dominated by 71,8%. Determinants of IDA Drug Distribution (p-value = 0,000, PR value = 2,498, 95% CI: 1,400-4,459), Willingness to Take Second IDA Drugs (p value = 0,000, PR value = 5,325, 95% CI:1,520-18,656), Assistance for Health Workers (p-value = 0,000, PR value = 2,690, 95% CI: 1,681-4,306), Agree to IDA drug distribution (p value = 0,008, PR value = 1,593, 95% CI: 0,778-3,259) has a significant relationship with IDA drug-taking behavior, and the logistic regression results of assisting health workers (OR = 76,002, 95% CI: 24,901-231,975) are the determinants most related to drug taking behavior IDA. It is necessary to assist health workers in the practice of taking IDA drugs in the next period. Health workers or health cadres must ensure that people take IDA drugs to increase treatment coverage, to accelerate the elimination of filariasis in Pekalongan City.